Clinical and Psychological Factors to Consider in Achieving Treatment-Free Remission in Patients With Chronic Myeloid Leukemia - Breccia, Massimo; Abruzzese, Elisabetta; Annunziata, Mario; Luciano, Luigia; Sica, Simona (Frontiers in Oncology, 2021)
Treatment of chronic myeloid leukemia (CML) has evolved dramatically in recent years. In this regard, the introduction of second-generation tyrosine kinase inhibitors (TKI) has revolutionized therapeutic goals, and it is now desirable to obtain treatment-free remission (TFR), i.e. when a patient who has stopped TKI therapy maintains a major molecular response and does not need to restart treatment. This report summarizes the main findings from a group of expert hematologists in Italy who met to discuss treatment and management of patients with CML with focus on broad-ranging aspects of TFR. A survey was used to obtain information about the clinicians’ experience with TFR and to better understand the clinical and psychological issues that patients and physicians face when considering TFR. The overall goal was to explore the possibility of discontinuing treatment from multiple points of view, considering both clinical aspects of TFR as well as psychological management of patients. Practical information is provided on aspects associated with initiating TFR, clinical data supporting it, the role of monitoring, and management of discontinuation-related adverse events. This publication outlines many of the shortcomings and highlights proposed solutions for routine clinical practice, and provides an overview of the literature relative to TFR.